Perbandingan Kebutuhan Koagulan Al2(So4)3 dan PAC Untuk Pengolahan Air Bersih Di WTP Sungai Ciapus Kampus IPB Dramaga - Prasetya, Pasca Eka; Saptomo, Satyanto Krido (Bumi Lestari; Vol 18 No 2 (2018)DO - 10.24843/blje.2018.v18.i02.p05, 2018)
Water Treatment Plant (WTP)  IPB process water from Ciapus River by water purifying process before distributed to consumers. The type of coagulant used is Al 2 (SO 4 ) 3 (aluminum sulfate) or alum and Polyaluminium Chloride (PAC). This study aimed to compare the water quality by using coagulant Al 2 (SO 4 ) 3   and PAC in WTP Ciapus River IPB Dramaga and to find out the optimum dosage of coagulant alum and PAC . This study used a test jar method and ISO (SNI) for the analysis of physical and chemical parameters of water. Based on the results of research, PAC was better than alum with the optimum dose of 20 ppm which produces 0.22 NTU of turbidity, 1 mg/l of TSS and 150 mg/l of TDS. While the optimum dose of alum was 20 ppm which generates 0.49 NTU of turbidity, 0 mg/l of TSS and 164 mg/l of TDS. Average costs for the use of coagulant alum and PAC were Rp. 95/m3 and Rp 215/m3, while the average value of the efficient used of coagulant alum and PAC were 91.34% and 83%. The results of both coagulants meets the criteria of water quality standards in accordance with Regulation of the Minister of Health No. 429 of 2010.